Acute and Subchronic Toxicity Assessment of 70% Ethanol Extract of Gendarusa Leaves In Vivo - Luthfiatu Kanina; Mabluhatus Solehah; Hani Plumeriastuti; Retno Widyowati; Bambang Prajogo Eko Wardoyo (Universitas Airlangga, 2022)
Background: Justicia gendarussa Burm. f., has been used traditionally in Indonesia for antifertility. Nowadays, a capsule containing 70% ethanol extract of J. gendarussa leaves has been studied for safety. Objective: This study aimed to determine the acute and sub-chronic toxicity of 70% ethanol extract of J. gendarussa leaves in vivo. Methods: In the acute toxicity study, a single dose of 2,000